Kesterite solar-cells by drop-casting of inorganic sol–gel inks. (15th September 2020) - Tseberlidis, Giorgio; Trifiletti, Vanira; Le Donne, Alessia; Frioni, Luigi; Acciarri, Maurizio; Binetti, Simona
Highlights: Cu2 ZnSnS4 thin films were deposited by direct drop-casting of the precursor solution. An in-depth characterization of both CZTS thin films and PV devices is discussed. The addition of KCl was experimentally demonstrated to improve device performance. SCAPS simulation was performed to deeply-understand the device behaviour. Abstract: The PV research is nowadays focused on finding low cost and easily processable thin-film materials, trying to move towards lighter and more versatile technologies. Among them, Cu2 ZnSnS4 (CZTS) drew the attention of the scientific community thanks to its structural similarity to the already reported and well-studied Cu(In, Ga)Se2 but with the great advantage to use cheap and earth-abundant elements. In this work, we report CZTS-based solar cells produced with a simple and straightforward sol–gel process, demonstrating how further expensive and industrially non-scalable instruments are not needed in order to provide a working device. Direct drop-casting of a precursor solution onto the substrate, followed by gelation and final annealing in Ar atmosphere, generates the desired phase of the material without any further source of sulphur. The precursor solution contains metal acetate salts which play a primary role in networking the metals in the gel matrix, together with thiourea and dimethylsulfoxide. With this methodology, only the strictly necessary amount of reagents is used saving until 2–3 orders of magnitude of starting materials compared to other wet deposition techniques and working devices were obtained showing η = 1.1%. The addition of KCl as a dopant into the precursor solution was proven to be beneficial for the grain growth and material quality, so the performance of the corresponding devices rises it up to η = 1.75%. The synthesised thin films have been fully characterised by UV–Vis absorption, μ-Raman, X-ray diffraction and Energy Dispersive Spectroscopy measurements. Their morphology has been investigated by Scanning Electron Microscopy, proving the high quality of the material. The so-produced PV devices with a standard SLG/Mo/CZTS/CdS/ZnO/AZO architecture show interesting and promising results, especially in terms of short circuit current density.